Diffusion features of aviation fuel fire in an obstructed nacelle. (28th September 2020) - Zheng, Yu; Cheng, Guanbing; Wang, Guoda; Li, Shuming
Accessory gearbox and electric engine control are important assemblies to keep an aircraft and its powerplant in good operation condition. The leaked aviation fuel fires probably lead to unsafe scenarios. In present paper, the physical and calculated models of a nacelle with AGB and EEC were constructed. Four slices were placed to trace changes and nephograms of thermal, kinetic and physiochemical parameters. The effects of AGB and EEC were examined on non-premixed flame diffusion properties. The results show that those thermal, kinetic and physiochemical parameters undergo transient and steady states. The effects of AGB on those parameters are more evident than those by EEC. In the transient state, temperature, velocity, and soot or CO concentrations increase originally and oscillate around one constant. To some extent, AGB prevents the diffused flame from propagating along the nacelle surfaces. However those parameter distributions are quasi-symmetrical. AGB and EEC amplify the oscillation of those parameters.